(untitled) (Polis (Santiago), 2018)
The current crisis we face is one of the first that generates global effects. It is linked to certain features characteristic of globalization. In this paper we propose some reading notes thereon. On one side, trying to unravel some features of the current crisis and the difficulties of the current political and social thought to account for it, situation that we link to an insufficient consideration of a framework from which to read the current events and social, economic, political and cultural. On the other hand, we analyze the need to articulate recognition, justice and accountability as guiding principles and a non-exclusive, perhaps only way of dealing with the trait (social, political, economic and cultural) of the primary and structural evolution of our societies in Latin America: inequality (and its corollary of injustice).